PENGEMBANGAN SOAL TES EVALUASI PEMBELAJARAN MENGGUNAKAN WORDWALL PADA MATERI KERAGAMAN BAHASA DAERAH DI INDONESIA - Siti Yunaryah, Nur Najmi Hashifah; Mulyawati, Yuli; Mirawati, Mira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Development of Evaluation Test Questions Using Wordwall on the Material of Regional Language Diversity in Indonesia. This research uses a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This research aims to develop, test the feasibility and test the effectiveness of the product. This research was conducted at SDN Cijujung 01 in class IV-A, totaling 32 students with the learning year in the even semester of 2024/2025. This research conducted a needs analysis by making observation instrument sheets, interviews, questionnaire assessments from media experts, linguists, material experts by lecturers, material experts by class teachers, teacher response questionnaires and student response questionnaires. The results showed that the learning evaluation test questions using wordwall in class IV-B SDN Cijujung 01 based on the average validation assessment of media experts obtained 100%, language experts obtained 96%, material experts by lecturers obtained 94% and material experts by teachers obtained 97% which was included in the “very feasible” category. The results of the student response questionnaire obtained 94% in the “very good” category and the average N-Gain score value obtained 0.66 in the moderate category. Based on the above results, it shows that the learning evaluation test questions using wordwall were developed to make learning more interesting and can improve student learning outcomes so that this learning is very feasible to use in schools. Keywords: Development, Learning Evaluation, Wordwall